Papers of Angus Denton - Denton, Angus (1991)
Papers relating to the theatre production "Harold" which was about the Aboriginal tenor, Harold Blair. The collection comprises correspondence, reports, production files, financial records, publicity matter, videos, photographs, posters, programs and order books.
Manuscript reference no.: MS Acc98.212.
Keywords: Denton, Angus -- Archives; Blair, Harold, -- 1924-1976.; Theater -- Australia